Direction-finding method solution phase ambiguity in determining the spatial orientation of space vehicle - Kartsan, I N; Petrosyan, M O; Efremova, S V; Khrapunova, V V (IOP conference series. Materials Science and Engineering, 2018)
When creating multichannel GNSS receivers that implement interferometric methods for measuring spatial orientation using GLONASS and GPS signals, the main problem is the resolution of phase ambiguity when measuring the phase difference for spatially separated antennas. In order to improve the accuracy of determining the spatial orientation, interferometers with the distance between the antennas (base length) reaching several meters are used. The ambiguity in measuring the phase shift is due to the fact that the wavelength of the measured signals is sufficiently small (about 19 cm), which is much smaller than the length of the bases of the interferometer. The methods for resolving phase ambiguity can be divided into two classes: one-stage ones that operate on the basis of the results of each measurement and methods based on filtering that require measurement of phase shifts over a certain time interval.